Cultivable microalgae diversity from a freshwater aquaculture filtering system and its potential for polishing aquaculture derived water streams - Couto, Ana T. (2022)
Aims: Microalgae are ubiquitous in aquatic environments, including aquaculture farms, but few studies have delved into their phytoplankton diversity and bioremediation potential. In this study, the cultivable phytoplankton of a rainbow trout freshwater aquaculture farm was isolated, phylogenetically analysed and used to assemble a consortium to polish an aquaculture derived effluent, with low concentrations of ammonium, nitrite and nitrate. Methods and Results: Through standard plating in different selective media, a total of 15 microalgae strains were isolated from sludge from a rotary drum filtering system which removes suspended solids from the water exiting the facility. Based on 18S rRNA gene sequences, isolates were assigned to nine different genera of the Chlorophyta phylum: Asterarcys, Chlorella, Chloroccocum, Chlorosarcinopsis, Coelastrella, Desmodesmus, Micractinium, Parachlorella and Scenedesmus. Species from most of these genera are known to inhabit freshwater systems in Galicia and continental Spain, but the Coelastrella, Asterarcys or Parachlorella genera are not usually present in freshwater streams. In an onsite integrative approach, the capacity of a consortium of native microalgae isolates to grow on aquaculture derived effluents and its nutrient removal capacity were assessed using a raceway pond. After 7 days, removal efficiencies of approximately 99%, 92% and 49% for ammonium, nitrite and nitrate, respectively, were achieved concomitantly with a microalgae biomass increase of ca. 17%. Conclusions: Sludge from the aquaculture filtering system presents a high diversity of microalgae species from the Chlorophyta phylum, whose application in a consortial approach revealed to be efficient to polish aquaculture derived effluents with low nutrient content. Significance and Impact of the Study: The use of native microalgae consortia from aquaculture systems can contribute to the development of efficient treatment systems for low nutrient wastewater, avoiding nutrients release to the environment and promoting water recirculation. This may further strengthen the use of phycoremediation at the industrial scale, as an environment friendly strategy.